Coram cruce oder cum cruce?: Gerhard Ebelings regulativer Gebrauch der theologia crucis - Stoellger, Philipp (Christology revised, 2024)
Gerhard Ebeling appeals centrally to the theology of the cross as regulative. Theology as a whole is to be characterized as theologia crucis; it is “interpretation of the cross.” In taking this approach, Ebeling was standing, at the same time, against a theology dominated by the incarnation or by the resurrection. In conversation with Ebeling, the ‘before the cross’ (coram cruce) must be thought further hermeneutically with regard to its interpretive potential. In the process, Ebeling’s own starting point will be investigated critically and at the same constructively by means of the ‘experience with the death of Jesus.’ Finally, it will be shown that Ebeling introduces the authoritative horizon of understanding of the cross from the standpoint of Easter and operates with a cum cruce rather than a coram cruce. Is it not the case that it is not theology of the cross that is being done here but rather a theology of the resurrection has been made to be the basic figure?
Gesehen am 30.01.2024